A small penguin cranium (Aves, Spheniscidae) from the Late Miocene of Bahía Inglesa Formation, Atacama Desert, Northern Chile - Acosta Hospitaleche, Carolina Ileana Alicia (2023)
A new cranium of penguin from the Late Miocene of the Bahía Inglesa Formation (Northern Chile) is described here. Specimen SGO.PV.22245 exhibits a unique combination of characters that suggests it belongs to a new species of either Eudypula Bonaparte, 1856, Spheniscus Brisson, 1760, or more probably to a more basal taxon related to them. The specimen is notably smaller than the fossil species of Spheniscus and more similar in size to the extant Spheniscus. The fossa glandulae nasalis narrows caudally, the crista nuchalis transversa and the crista temporalis are expanded like short wings, and a short crista nuchalis sagittalis connects with the rounded and cranially projected eminentia cerebellaris. The fossa temporalis is subtriangular and deeper caudally and the cranial roof is widely expanded. All these features approach the condition to some species of Spheniscus and Eudyptula. However, because of the incompleteness of the material and the fact that it cannot be compared with some fossil species of Spheniscus only known through postcranial material, we are not able to provide a more accurate assignment.